Curriculum Development in Indonesia (2014–2024): A Bibliometric Analysis of Research Trends and Scholarly Characteristics - Gilang Ramadhan; A. Sobandi; Heni Mulyani; Toni Heryana (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
The curriculum is a guideline for implementing education. Indonesia has experienced 11 curriculum changes. This study uses bibliometric analysis to examine the trends and characteristics of curriculum development in Indonesia. This bibliometric analysis method is carried out by collecting articles in the Dimensions database, which are processed using VOSviewer. The number of articles collected was 431, which were then filtered into 426 articles. This bibliometric analysis uses two approaches: performance analysis (journals, publication institutions, and educational organizations) and science mapping (citations, co-citations, bibliographic merging, and keywords). The results found that the number of curriculum development publications in Indonesia from 2014 to 2024 tended to increase. Universitas Pendidikan Indonesia, Universitas Negeri Padang, and Universitas Sebelas Maret have the highest publications on curriculum development. The keyword Development gets the highest occurrence value of 94. 2020 is the year with many keywords appearing, namely 24 keywords. This research is expected to encourage and increase innovation in curriculum development research in Indonesia